2017
DOI: 10.18203/2320-1770.ijrcog20170076
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of obstetricians regarding labour analgesia and limitations in practising it

Abstract: Background: Parturient experience labour pain of varying degrees which intensifies as labour progresses. Providing adequate pain relief during labour is important for positive experience of child birth.Methods: This cross-sectional survey was conducted among obstetricians working in five teaching hospitals in Tamil Nadu in 2015. Obstetricians working in these medical colleges were given structured questionnaire to be filled by them. It had questions regarding the obstetricians knowledge, experience and attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…In our study, most participants have shown negative attitude towards labour analgesia which is in contrast to other studies (2,21,34) . Major reason stated by our participants as barriers are lack of awareness of maternal health care providers, labour pain is not a priority, and labour pain and analgesia is not included as part of their training program.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, most participants have shown negative attitude towards labour analgesia which is in contrast to other studies (2,21,34) . Major reason stated by our participants as barriers are lack of awareness of maternal health care providers, labour pain is not a priority, and labour pain and analgesia is not included as part of their training program.…”
Section: Discussioncontrasting
confidence: 99%
“…Among those, health care provider related barriers are the main barriers, the easiest to be assessed and measured, and to be corrected in many low and middle-income countries such as Ethiopia. A lack of knowledge, poor attitudes, and unavailability of labour analgesia options are considered to be the main barriers that influences utilization of labour analgesia in low resource settings (2,(21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%
“…However, in other settings, opioids are routinely offered to women in the early stages of labour [2931]. Parenteral opioids are reported to be commonly prescribed by Indian obstetricians [10]. In Nigeria, two separate surveys confirmed the demand and acceptability of use of opioids for labouring women by various cadres of healthcare providers [32, 33] .…”
Section: Discussionmentioning
confidence: 99%
“…In low resource settings, pain management options (especially pharmacological options) are not well-established and the provision of pain relief options often depends on the health system capacity, the knowledge and attitudes of healthcare providers and availability and cost of medications [10–14]. Healthcare providers can play a positive role by educating women about the options available and supporting their choice in coping with labour pain; or a negative role by demonstrating disrespectful care, withholding care and lack of communication [11, 12, 14] .…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh health care providers perceive labor pain is a natural process and recommending labor analgesia is unnecessary but they rely on providing continuous labor support [11]. In India 55% of respondents were provide epidural labor analgesia [12]. Utilization of labor analgesia in different countries of Africa showed 48.4% in Zara Nigeria [13], 49% in Nigeria [14], 44.9% in Egypt [1] and 3.3% in Kenya [15].…”
Section: Introductionmentioning
confidence: 99%